A Comprehensive Review of Niobium Nanoparticles: Synthesis, Characterization, Applications in Health Sciences, and Future Challenges - Muhammad Usman Khalid; Austeja Rudokaite; Alessandro Marcio Hakme da Silva; Monika Kirsnyte-Snioke; Arunas Stirke; Wanessa C. M. A. Melo (Nanomaterials)
Niobium nanoparticles (NbNPs) have gained attention as promising materials in biomedical applications due to their exceptional biocompatibility, corrosion resistance, and versatility. These nanoparticles offer potential in drug delivery, imaging, and tissue engineering, where their nanoscale properties allow precise interactions with biological systems. Among niobium-based nanomaterials, niobium pentoxide (Nb2O5) is the most extensively studied due to its chemical stability, bioactivity, and optical properties. Nb2O5 nanoparticles have shown significant potential in catalysis, biosensing, and photodynamic therapy, as their stability and reactivity make them ideal for functionalization in advanced biomedical applications. Despite these advantages, challenges remain regarding the biodegradability and long-term retention of NbNPs in biological systems. Their accumulation in tissues can lead to risks such as chronic inflammation or toxicity, emphasizing the importance of designing nanoparticles with controlled clearance and biodegradability. Surface modifications, such as coatings with biocompatible polymers, have demonstrated the ability to mitigate these risks while enhancing therapeutic efficacy. This review provides a comprehensive overview of NbNPs, with a focus on Nb2O5, highlighting their unique properties, current biomedical applications, and limitations. By addressing the remaining challenges, this work aims to guide the development of safer and more effective niobium-based nanomaterials for future medical innovations.